Speciation of uranium and radionuclides in the bottom sediments of premises 001/3 of the "Shelter" object - O. O. Odintsov; L. A. Palamar; L. B. Chikur (Ядерна фізика та енергетика)
The results of experimental determination of the forms of uranium and radionuclides 90Sr, 137Cs, 154Eu, 238Pu, 239+240Pu, 241Am, and 244Cm in the bottom sediments of the premises 001/3 of the "Shelter" object are presented. By the sequential extraction procedure, the following amounts are determined: water-soluble, exchange, carbonate, and acid-soluble forms of uranium, fission products (90Sr, 137Cs, 154Eu), and transuranium elements (238Pu, 239+240Pu, 241Am, 244Cm) in the bottom sediments in the premises 001/3 on a mark of -2.60 m of auxiliary systems of the reactor compartment of the "Shelter" object. The concentration of uranium in the bottom sediments of room 001/3 is 3.1 ± 0.5 g/kg. Specific activity of 90Sr, 137Cs in the bottom sediments is within the range of 6·108 - 1·109 Bq/kg, and 239+240Pu and 241Am within the range of 6·105 - 8·106 Bq/kg. Radionuclides 90Sr, 137Cs, 154Eu, 238Pu, 239+240Pu, 241Am, 244Сm in the bottom sediments are in different chemical forms that will define their different potential mobility. Uranium and 137Cs in the bottom sediments of premises 001/3 mainly are in exchange forms. The amount of water-soluble forms of uranium and cesium is 1.5 - 3 %. The basic amount of 90Sr, more than 60 %, is carbonate soluble in a weak acid at рН 4.8. More than 65 % of 238Pu and 239+240Pu in the bottom sediments are in acid-soluble forms. The mobility of 154Eu, 241Am and 244Cm in the bottom sediments is much higher than that of plutonium; at pH 4.8 more than 40 % of 241Am go to soluble state. The ratio between the activities of 137Cs/90Sr, 90Sr/239+240Pu, 241Am/239+240Pu, and 244Cm/239+240Pu in the bottom sediments considerably differ from the analogical relations of radionuclides in a fuel containing materials of the "Shelter" object.